Hubungan Diare dan Infeksi Saluran Pernafasan Atas (ISPA) Terhadap Kejadian Stunting Pada Balita Usia 13-59 Bulan Di Puskesmas Tamangapa - Akbar, Nurlina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Stunting is a serious problem that threatens the next generation of the nation that can hamper physical, mental growth and decline in children's intelligence. In 2019, the stunting rate of South Sulawesi was 30.5% and the Makassar City area was 8.62%. The incidence of stunting is not only caused by nutritional factors but also the health factor of the child itself. Risk factors for stunting include upper respiratory tract infections and diarrhea. This study was conducted to determine the relationship and risk of diarrhea and upper respiratory tract infections until it can cause stunting in toddlers aged 13-59 months. This research was an analytic survey with a cross sectional design through a retrospective approach. Samples were selected by purposive sampling inclusion criteria, toddlers aged 13-59 months with z-score values